Predictive response to the behaviour of old structures using ambient vibrations - Zoubida Maraf; Mounir Naili; Mohamed Bensoula; Abderrahmane Kibboua; Missoum Missoum (The Journal of Engineering and Exact Sciences)
The response of ancient structures such as the Saint-Jean-Baptiste church or the current El-Badr mosque in Mostaganem (Algeria) to earthquakes depends on these physical characteristics and consequently on modal properties such as frequencies, damping and modal deformations. In this paper, ambient vibration tests were carried out on the three parts of the mosque building, and the response spectra and damping obtained will be correlated with the mechanical tests carried out in the second part of the work. Determination of the dynamic characteristics made it possible to distinguish differences in stiffness and to clearly highlight a disparity in frequencies in each structure, which may correspond to the age of each part of the building, the design and construction and differences in levels, etc. The results of the destructive tests give indications that confirm the hypotheses of ageing of the materials. The low young modulus of the various components partly confirms the frequency and damping values obtained. The experimental study of the mosque using ambient vibrations will give an order of magnitude of the vibratory mode periods, which are the first steps in any modelling, reinforcement and/or verification strategy and constitute a health record for this type of heritage.